Plataforma de e-recruitment - Novas estratégias para o recrutamento online - Olímpio Luís Malojo Ferreira (2016)
The search for the best curriculum for the needs of the Human Resources, as well find job postings that matches the expectations of job seekers, motivated the development of a model that responds effectively to these needs. This dissertation seeks to investigate and specify a platform that hopes to come to enhance the matching between job opportunities and candidates, integrated various modules, including the Serious Games as tools for skills assessment. To achieve goals of this work, we used the concept of Job Matching, which is in recrutemanto area and selection, an area with high potential for application at the level of creating innovative mechanisms that enable to carry out a recruitment and initial selection of potential candidate choices correspond to the expectations that recruiters aspire for each job opportunity. For the percussion of the objectives of this work, we used the concept of Job Matching, which is in recrutemanto area and selection, an area with high potential for application at the level of creating innovative mechanisms that enable to carry out a recruitment and initial selection potential choices of candidates who meet the expectations that recruiters aspire for each job opportunity. I try so present the guidelines and the main features of a reference model for building a platform for online employment advertising opportunities and matching candidates, supported by Serious Games tools for evaluating the form of skills to achieve the objectives intended.